Applying geobia method to analyze climate changes associated to energy generation - analysis about oil exploration onshore at potiguar basin - Alves, A.M. (2020)
This paper deals with the discussion of the analysis of remote sensing data on onshore oil exploration occurring in the Potiguar Basin, in the state boundaries of Rio Grande do Norte - Brazil, from the perspective of changes in albedo index, surface reflectance and surface temperature associated with to those aspects. The albedo is considered a significant variable in understanding the energy balance that makes up an important element of the analysis of global climate change. Through the use of remote sensing tools and GIS, based on surface reflectivity algorithms and surface temperature from GEObia (GEOgraphic-Object-Based Image Analysis) from the sequence - Pan-sharpened composite, Radiance with atmospheric correction, Reflectance with atmospheric correction, and Surface temperature with emissivity correction, used in scenes produced by OLI sensors (Operational Land Imager) and TIRS (Thermal Infrared Sensor) Landsat-8 satellite, it was possible to determine the variations in surface reflectance and surface temperature, and compare them to index albedo therein the oilfield based on the method 6S + Liang (2000). The research indicates, with the determination of processed values, which areas of oil exploration to the analyzed time, present significant change rates, with a tendency to increase in reflectance and temperature associated with albedo changes, as well as other areas of renewable energy exploration.